FISCAL POLICY FRAMEWORK IN A DECARBONIZED FUTURE FOR RESOURCE-RICH COUNTRIES - Elmir Eyvaz-Zada (Agora International Journal of Economical Sciences (AIJES), 2024)
In a world transitioning towards decarbonization, resource-rich countries (RRCs) face unique challenges in shaping their fiscal policy frameworks, necessitating significant adjustments. This paper analyzes the effects of decarbonization on the fiscal policies of RRCs, focusing on the intersection of fiscal sustainability and sustainable development goals. The key findings reveal that effective fiscal discipline is crucial for maintaining fiscal sustainability amid fluctuating resource revenues. Implementing medium-term budget frameworks helps RRCs manage economic volatility and plan for long-term fiscal health. The adoption of green fiscal policies can support RRCs in navigating the challenges of decarbonization, contributing to both fiscal sustainability and sustainable development goals. Additionally, decarbonization affects various economic aspects, including budget revenues, expenditures, and the overall fiscal sustainability landscape, necessitating tailored fiscal policies. This comprehensive analysis provides valuable insights into designing and implementing fiscal policies suited to the needs of resource-rich countries during the global energy transition. The study highlights how green fiscal policies can assist RRCs in managing decarbonization challenges while achieving sustainable development goals.
Keywords: 330